Hydrogen permeation properties of CrxCy@Cr2O3/Al2O3 composite coating derived from selective oxidation of a CrC alloy and atomic layer deposition. (8th November 2018) - Wang, Jipeng; Lu, Zhaoxia; Ling, Yunhan; Wang, Rongguang; Li, Yunhui; Zhou, Qingyun; Zhang, Zhengjun
Abstract: Metal oxides and carbides are promising tritium permeation barrier coatings for fusion reactors. However, the thermomechanical mismatch between the coating and substrate poses a threat to their interface's integrity during fabrication and operation. To address this issue, a metallic interlayer coating was introduced followed by selective oxidation in which a compact and uniform CrC amorphous alloy coating was successfully deposited on the stainless steel substrate by pulsed electrochemical deposition. A new composite coating of Crx Cy @Cr2 O3 /Al2 O3 was formed by subsequent controlled oxidation conversion and atomic layer deposition. The phase, morphology, chemical state and defects of the films were analyzed and compared both before and after hydrogen exposure at 300 °C. The results show that this new kind of composite coating, based on the principles of grain boundary pinning of chromic oxide with carbide and defect healing of alumina, can remarkably improve the hydrogen permeation barrier performance of these materials. Highlights: A new ceramic coating based on grain boundary pinning and passivation for hydrogen permeation barrier was proposed. The Crx Cy @Cr2 O3 /Al2 O3 coating was successfully fabricated by selective oxidation of a CrC alloy and atomic layer deposition. This composite coating demonstrates improved and repair performance upon hydrogen exposure.